Creating a Digital Psychoeducation Programme for bipolar disorder in the COVID-19 pandemic. (1st June 2022) - Gadelrab, R.; Simblett, S.; Hook, J.; Rickwood, S.; Martinez, J.; Johnstone, M.; Flower, C.; Bourne, S.; Young, A.; Macritchie, K.
Abstract : Introduction: The Covid-19 pandemic profoundly affected delivery and accessibility of mental health care services at a time when most needed. The OPTIMA Mood Disorder Service, a specialist bipolar disorder service, adapted group psychoeducation programme for delivery on-line. Objectives: We report the feasibility of creating a digital psychoeducation programme. Methods: The OPTIMA ten session group psychoeducation programme was converted into a 'Digital' intervention using video-conferencing. Sessions offered a range of key topics, derived from the initial Barcelona Group Psychoeducation Programme. At the time of writing, OPTIMA had fully completed two 10 session digital courses. Results: A total of 12 people (6 in each group) consented to be part of a service evaluation of the digital groups. Just over half of the participants were women (7/12; 58.3%) and one identified as being non-binary (8.3); remaining participants were men. Age of participants ranged from 25 years to 65 years (Mean=42.3; SD=13.1). Data showed a high level of engagement (77%) All participants reported some improvement with a mean Bipolar Self-Efficacy scale (BPSES) post-group score of 105.6 (SD=14.8). At group level, this change was not statistically significant (F (1, 15) = 0.71, p=0.41). At an individual level, two out of five showed a reliable change index >1.96. Conclusions: Delivering a 'digital' group psychoeducation programme was possible due to careful planning and programme development. There was good uptake from service users suggesting it is a feasible approach with preliminary evidence of clinical benefit. Disclosure: No significant relationships.